Wireless power transfer using multiple-transmitters for high stability for position - Kazuma Onishi; Kazuya Yamaguchi; Kenichi Iida (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The aim of this study is to optimize the system in the wireless power supply using multiple transmitters by algebraically analyzing the effects of both a circuit parameters and an axis displacement, etc. In addition to these analyses, the other aim is designing, producing and evaluating wireless charger with high stability for position. In the proposed method, we analyzed the situation in which three transmitters are used as power sources. It is turned out that the optimum arrangement of three transmitters is equilateral triangular from Biot-Savart law and circuit equation. In the experiment, transmitted power is measured when the receiver is moved on the vertical plane in regard to central axis of coils. It is confirmed that 4~4.5mW is transmitted at the face-to-face of transmitters and 2.4mW is transmitted at the center of transmitters.